2014
DOI: 10.3892/or.2014.3132
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of heat shock proteins 90 and 70 promotes cell death and enhances the anticancer effect of chemotherapeutic agents in bladder cancer

Abstract: Heat shock proteins (HSPs), which are molecular chaperones that stabilize numerous vital proteins, may be attractive targets for cancer therapy. The aim of the present study was to investigate the possible anticancer effect of single or dual targeting of HSP90 and HSP70 and the combination treatment with HSP inhibitors and chemotherapeutic agents in bladder cancer cells. The expression of HSP90 and the anticancer effect of the HSP90 inhibitor 17-N-allylamino-17-demethoxygeldanamycin (17-AAG) coupled with cispl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 44 publications
0
33
0
7
Order By: Relevance
“…Preclinical studies suggest that Hsp90 inhibitors are able to enhance the efficacy of anticancer agents, and potentially overcome drug resistance. 2830 Several studies have been conducted with Hsp90 inhibitors in combination with cytotoxic chemotherapies including the GALAXY-I study of ganetespib with docetaxel in advanced non–small-cell lung cancer, which demonstrated improved OS with docetaxel with ganetespib compared with docetaxel alone as second line therapy. 30 These data, along with unpublished preclinical data suggesting strong synergy of ganetespib with platinum in CRC cell lines and xenografts support our plans for a combination study in metastatic CRC particularly in KRAS-mutated CRC where we believe Hsp90 might have the most potential benefit based on preclinical data.…”
Section: Resultsmentioning
confidence: 99%
“…Preclinical studies suggest that Hsp90 inhibitors are able to enhance the efficacy of anticancer agents, and potentially overcome drug resistance. 2830 Several studies have been conducted with Hsp90 inhibitors in combination with cytotoxic chemotherapies including the GALAXY-I study of ganetespib with docetaxel in advanced non–small-cell lung cancer, which demonstrated improved OS with docetaxel with ganetespib compared with docetaxel alone as second line therapy. 30 These data, along with unpublished preclinical data suggesting strong synergy of ganetespib with platinum in CRC cell lines and xenografts support our plans for a combination study in metastatic CRC particularly in KRAS-mutated CRC where we believe Hsp90 might have the most potential benefit based on preclinical data.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, HSP70 overexpression possibly contributes to the avoidance of cell death, and HSP70 could be a key molecule for overcoming resistance to HSP90 inhibitors. Indeed, the combination of these two chaperones with conventional anti-cancer drugs is a promising therapeutic option for patients with advanced bladder cancer (Ma et al 2014). HSP70 is a potential biomarker for the detection of tumors and for monitoring the clinical outcome of radiotherapy in squamous cell carcinoma of the head and neck (SCCHN) patients (Gehrmann et al 2014b).…”
Section: Changes In the Significance Of Hsp70 Levels In Various Cancersmentioning
confidence: 98%
“…The chaperone-rich cytoplasm of the cancer cell thus contributes to the resistance to PCD and killing by cytotoxins [49]. Chaperones appear to act additively in the restraint of cell death and for instance dual targeting of Hsp70 and Hsp90 promoted chemotherapy-induced death in bladder cancer[50]. …”
Section: Hsps and The Defining Traits Of Cancer Cellsmentioning
confidence: 99%